ToxGen: an improved reference database for the identification of type B-trichothecene genotypes in Fusarium - Kulik, Tomasz (2017)
Type B trichothecenes, which pose a serious hazard to consumer health, occur worldwide in grains. These mycotoxins are produced mainly by three different trichothecene genotypes/chemotypes: 3ADON (3-acetyldeoxynivalenol), 15ADON (15- acetyldeoxynivalenol) and NIV (nivalenol), named after these three major mycotoxin compounds. Correct identification of these genotypes is elementary for all studies relating to population surveys, fungal ecology and mycotoxicology. Trichothecene producers exhibit enormous strain-dependent chemical diversity, which may result in variation in levels of the genotype’s determining toxin and in the production of low to high amounts of atypical compounds. New high-throughput DNA-sequencing technologies promise to boost the diagnostics of mycotoxin genotypes. However, this requires a reference database containing a satisfactory taxonomic sampling of sequences showing high correlation to actually produced chemotypes. We believe that one of the most pressing current challenges of such a database is the linking of molecular identification with chemical diversity of the strains, as well as other metadata. In this study, we use the Tri12 gene involved in mycotoxin biosynthesis for identification of Tri genotypes through sequence comparison. Tri12 sequences from a range of geographically diverse fungal strains comprising 22 Fusarium species were stored in the ToxGen database, which covers descriptive and up-to-date annotations such as indication on Tri genotype and chemotype of the strains, chemical diversity, information on trichothecene-inducing host, substrate or media, geographical locality, and most recent taxonomic affiliations. The present initiative bridges the gap between the demands of comprehensive studies on trichothecene producers and the existing nucleotide sequence databases, which lack toxicological and other auxiliary data. We invite researchers working in the fields of fungal taxonomy, epidemiology and mycotoxicology to join the freely available annotation effort.